THE READINESS OF TEACHERS ON BLENDED LEARNING TRANSITION FOR POST-COVID-19 PERIOD: AN ASSESSMENT USING PARALLEL MIXED METHOD - Anoba, Jeorge Louie D; Cahapay, Michael B (PUPIL: International Journal of Teaching, Education and Learning, 2020)
Technology is seen by many as the “holy grail” that will address the constraints brought by the Coronavirus Disease 2019 (COVID-19) to the educational systems. The success, however, depends in part on the readiness of the teachers. This paper comprehensively assessed the readiness of teachers specifically on blended learning transition amid the COVID-19 crisis. Employing parallel mixed-method research, it involved elementary teachers from Carpenter Hill Elementary School, Mindanao, Philippines. The researchers used a survey questionnaire and interview guide data. This work revealed points of convergence, elaboration, and divergence in the data sets. An interesting point further underscored is that some quantitative and qualitative results may diverge, but challenges in these facets of blended learning can be turned into opportunities for teachers in the conduct of blended learning. A responsive, appropriate, and relevant teacher preparation program should be developed based on this evidences toward an efficient and effective instructional implementation in the future.